2011
DOI: 10.2215/cjn.09301010
|View full text |Cite
|
Sign up to set email alerts
|

Early Start of Dialysis

Abstract: SummaryIn the US, patients who initiate dialysis "early" (at Modification of Diet in Renal Disease estimated GFR [eGFR]> 10 ml/min per 1.73m 2 ) account for over 50 percent of new dialysis starts. This trend to an early start is based on conventional wisdoms regarding benefits of dialytic clearance, that albumin levels are nutritional markers, and early dialytic therapy is justified to improve nutrition especially in diabetics and that waiting until low levels of eGFR (i.e., <6 ml/min per 1.73m2 ) may be dange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
88
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 74 publications
1
88
0
4
Order By: Relevance
“…In addition, there has been a trend for earlier initiation of dialysis in several countries (8)(9)(10)16). In the United States, the percentage of new dialysis starts with an eGFR .10 ml/min per 1.73 m 2 in patients with diabetes and without diabetes increased from 25% to 55% and from 16% to 48%, respectively, between 1996 and 2008 (17). In Canada between 2001 and 2007, mean eGFR at the time of dialysis initiation increased from 9.3 to 10.2 ml/min per 1.73 m 2 , and the proportion of early starts rose from 28% to 36% (9).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there has been a trend for earlier initiation of dialysis in several countries (8)(9)(10)16). In the United States, the percentage of new dialysis starts with an eGFR .10 ml/min per 1.73 m 2 in patients with diabetes and without diabetes increased from 25% to 55% and from 16% to 48%, respectively, between 1996 and 2008 (17). In Canada between 2001 and 2007, mean eGFR at the time of dialysis initiation increased from 9.3 to 10.2 ml/min per 1.73 m 2 , and the proportion of early starts rose from 28% to 36% (9).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in practice patterns leading to the decrease in early starts were influenced by well designed, patientoriented research informing conversations with patients around the timing of and need for renal replacement therapy. [9][10][11][12][13][14][15][16][17][18][19] The knowledge gained from these studies and others about the pros and cons of therapy options, including maximum conservative management, should be incorporated into patient-centered, age-relevant decision aids, a tool that is successful in helping patients understand the effect of various options on their healthcare goals and personal priorities. 20,21 Unfortunately, many elderly patients do not decide whether to pursue renal replacement therapy while they are in calm, controlled preemptive settings.…”
mentioning
confidence: 99%
“…1 This trend appears to have been based on conventional wisdom unsupported by peer-reviewed publications. 2 Several articles, including the IDEAL (Initiation of Dialysis Early and Late) randomized controlled trial and observational studies based on national and international dialysis registries, failed to show a survival benefit for early dialysis initiation. 2 Couchoud et al reported that after adjustment for socioeconomic and medical risk factors, treatment incidence increases as a result of early start.…”
mentioning
confidence: 99%
“…2 Several articles, including the IDEAL (Initiation of Dialysis Early and Late) randomized controlled trial and observational studies based on national and international dialysis registries, failed to show a survival benefit for early dialysis initiation. 2 Couchoud et al reported that after adjustment for socioeconomic and medical risk factors, treatment incidence increases as a result of early start. 3 We report on the most recent U.S. Renal Data System (USRDS) incident data that show a possible reversal of the early-start trend.…”
mentioning
confidence: 99%